A method for calculation of finite fatigue life under multiaxial loading in high-cycle domain (Fracture and Structural Integrity, 2014)
A method for fatigue life assessment in high-cycle domain under multiaxial loading is presented in this paper. This approach allows fatigue assessment under any kind of load history, without limitations. The methodology lies on the construction - at a macroscopic level - of an “indicator” in the form of a set of cycles, representing plasticity that can arise at mesoscopic level throughout fatigue process. During the advancement of the loading history new cycles are created and a continuous evaluation of the damage is made.
Keywords: High-cycle multiaxial fatigue